2007
DOI: 10.1590/s1413-86702007000500004
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution syndrome in patients treated for HIV and tuberculosis in Rio de Janeiro

Abstract: examine cases of immune reconstitution syndrome (IRS) and its incidence rate in tuberculosis (TB)-human immunodeficiency virus (HIV) coinfected patients. The incidence rate (IR) was calculated using a Poisson regression. The confidence interval (CI) that was stipulated was 95%. IRS occurred in 10/84 HIV and TB-positive patients; nine of them were on highly active anti-retroviral therapy (HAART) during a mean of 61.7 (±59) days following the introduction of antiretrovirals. Lymph-node enlargement was the sole c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 16 publications
5
24
0
Order By: Relevance
“…of patients with HIV-TB coinfection develop IRD (11,13,15,71,77,102,104,128,129,149), beginning as early as 5 days after starting ART (116). Most patients develop symptoms within the first 2 to 6 weeks (71,77,104,128,129), though cases may occur after 1 to 4 years (58,62,129).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…of patients with HIV-TB coinfection develop IRD (11,13,15,71,77,102,104,128,129,149), beginning as early as 5 days after starting ART (116). Most patients develop symptoms within the first 2 to 6 weeks (71,77,104,128,129), though cases may occur after 1 to 4 years (58,62,129).…”
Section: Introductionmentioning
confidence: 99%
“…Most patients develop symptoms within the first 2 to 6 weeks (71,77,104,128,129), though cases may occur after 1 to 4 years (58,62,129).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently studies from India [16], Thailand [17], South Africa [18 ] and Brazil [19 ] have been published. These studies found substantially lower rates of TB IRD with 8, 13, 12 and 12% of patients, respectively, being affected.…”
Section: Rates and Risk Factors For Tuberculosis Immune Reconstitutiomentioning
confidence: 99%
“…These rates include the predominance of localized (paucibacillary) lymph node disease [16,19 ], comparatively high baseline CD4 cell counts [16], or delayed initiation of ART [17,18 ,19 ]. The timing of ART has a particularly important impact on risk of IRD (Fig.…”
Section: Rates and Risk Factors For Tuberculosis Immune Reconstitutiomentioning
confidence: 99%